Using make beliefs comix platform to improve sentences construction in writing skills - Briones Zambrano, Mariana Marisol (2022)
Nowadays, most people use electronic devices, and technology is a fantastic gift developed by computer geniuses. Therefore, English became one of the most popular foreign languages globally. (Raja & Nagasubramani, 2018) Communicate, writing is a skill that people use in their daily lives to communicate. However, some people do not want to express the same thing in spoken language to express their thoughts, feelings, experiences, and emotions, make sense of complex and abstract ideas, and learn to communicate with other people daily.